2007
DOI: 10.1093/hmg/ddm290
|View full text |Cite
|
Sign up to set email alerts
|

Human angiogenin is a neuroprotective factor and amyotrophic lateral sclerosis associated angiogenin variants affect neurite extension/pathfinding and survival of motor neurons

Abstract: Amyotrophic lateral sclerosis (ALS) is a late onset neurodegenerative disorder affecting upper and lower motor neurons (MNs). The molecular mechanisms underlying ALS are poorly understood. Mutations in SOD1 is one of the known causes of ALS but occur only in a very small number of cases of ALS. Interestingly, mutations in human angiogenin (hANG), a member of the ribonuclease A (RNase A) superfamily known to be involved in neovascularization, have been recently reported in patients with ALS, but the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 57 publications
6
101
1
Order By: Relevance
“…ANG protects mouse P19 embryonal carcinoma cells (26) and cultured mouse motor neurons from stress-induced apoptosis (27,28). Human motor neurons (hMNs) differentiated from ES cells express the motor neuron markers TUJ1, MAP2, SMI-32, and peripherin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ANG protects mouse P19 embryonal carcinoma cells (26) and cultured mouse motor neurons from stress-induced apoptosis (27,28). Human motor neurons (hMNs) differentiated from ES cells express the motor neuron markers TUJ1, MAP2, SMI-32, and peripherin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent studies have suggested that angiogenin is an important neurodevelopmental protein with neuroprotective properties, and that mutant ANG impairs neurite outgrowth. [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The ribonuclease A activity has been shown to be reduced or lost in ANG mutant proteins. ANG is a potent inducer of neovascularization in vivo and has been shown to play a key role in neurite outgrowth and pathfinding during early embryonic development (Subramanian et al 2008). Its structure and function are partially homologous to that of vascular endothelial cell growth factor (VEGF); a previously reported genetic susceptibility and disease modifying factor in the development of neurodegeneration (Lambrechts et al 2009), and both VEGF and ANG have been shown to be neuroprotective.…”
Section: Als9: Angiogenin (Ang)mentioning
confidence: 99%